"I Am a Caregiver": Sense-making and Identity Construction through Online Caregiving Narratives. Issue 2 (3rd April 2021) - Cooper, R. Amanda
ABSTRACT: The all-consuming role and responsibilities of providing care to an aging parent or spouse create identity disruption and stress. However, this stress may be resolved as family caregivers integrate the role of caregiver into their identity and construct an aspect of their identity around providing care (i.e., caregiver identity). Rooted in the retrospective heuristic of communicated narrative sense-making theory (CNSM), this paper investigates the identities family caregivers construct through online narratives about their caregiving experiences. Using thematic narrative analysis to analyze a corpus of 40 online narratives, this study yielded four distinct caregiver identities: the prisoner, which is defined by a sense of being trapped by the responsibility of caregiving; the crumbling caregiver, which focuses on extreme exhaustion in providing care; the companionate caregiver, which focuses on the relational aspects of providing care; and the redeemed caregiver, which is defined by growth through difficulty.